Združba z vrsto Festuca rubra kot dominantno vrsto na cestnih brežinah - Šilc, Urban (Hladnikia (Ljubljana), 2001)
The paper present the basal community Festuca rubra-Arrhenatheretalia/Artemisietea that was found on highway slopes. The author also proposes the Slovene terminology for the deductive classification system.
Keywords: cestne brežine; fitocenologija; phytosociology; rastlinske združbe